Socialising kitties: A quantitative survey of US cat owner attitudes towards kitten and adult cat socialisation programmes - Jennifer K Link; Carly M Moody (Animal Welfare)
Socialisation is important for normal social and behavioural development in companion animals. However, little research has focused on kitten socialisation or owner attitudes towards kitten socialisation programmes. Thus, we used a quantitative online survey to describe US cat owner attitudes towards kitten socialisation and elucidate aspects of socialisation programmes deemed important by owners. Questions (n = 45) included participant demographics, participant experiences with socialisation, information regarding participants’ cats (Felis catus), where participants receive socialisation information, and rating the importance of socialisation components. Participants were recruited via advertisements posted on social media and an online news article. Of the 2,238 responses, participants were most frequently women (74.7%), owning two cats (38.0%), who had not worked with cats professionally (72.9%). Most participants had not heard of socialisation programmes for kittens (69.3%), but would be interested in enrolling in a future programme (50.4%). Participants indicated important aspects of kitten socialisation programmes as: education about reducing problem behaviours (87%); understanding cat body language (85.8%); and getting kittens used to handling (83.1%). A logistic regression revealed that the presence of aggression in their current cat predicted interest in a future programme, as well as living in an urban or suburban area. These results suggest a lack of owner awareness of kitten socialisation, and indicate many owners are interested in enrolling in a future kitten socialisation programme. Further research should explore methods to improve access to kitten socialisation information, elucidate components of current socialisation programmes, and assess their impact on owner management and cat behaviour.